The aminoindanol core as a key scaffold in bifunctional organocatalysts - G. Sonsona, Isaac; Marqués-López, Eugenia; Herrera, Raquel P. (Beilstein Journal of Organic Chemistry, 2016)
The 1,2-aminoindanol scaffold has been found to be very efficient, enhancing the enantioselectivity when present in organocatalysts. This may be explained by its ability to induce a bifunctional activation of the substrates involved in the reaction. Thus, it is easy to find hydrogen-bonding organocatalysts ((thio)ureas, squaramides, quinolinium thioamide, etc.) in the literature containing this favored structural core. They have been successfully employed in reactions such as Friedel–Crafts alkylation, Michael addition, Diels–Alder and aza-Henry reactions. However, the 1,2-aminoindanol core incorporated into proline derivatives has been scarcely explored. Herein, the most representative and illustrative examples are compiled and this review will be mainly focused on the cases where the aminoindanol moiety confers bifunctionality to the organocatalysts.
Keywords: aminocatalysis; 1,2-aminoindanol; bifunctional; organocatalysis; hydrogen bonding

(untitled) - Weix, D. J.; Ellman, J. A. (Org. Lett., 2003)

(untitled) - Lazar, A.; Sharma, P.; Singh, A. P. (Microporous Mesoporous Mater., 2013)

(untitled) - Dai, X.; Cahard, D. (Adv. Synth. Catal., 2014)

(untitled) - Sani, M.; Volonterio, A.; Zanda, M. (ChemMedChem, 2007)

(untitled) - Piras, M.; Fleming, I. N.; Harrison, W. T. A.; Zanda, M. (Synlett, 2012)

Asymmetric Organocatalysis: From Biomimetic Concepts to Applications in Asymmetric Synthesis - Berkessel, A.; Gröger, H. (Wiley-VCH, 2005)

Enantioselective Organocatalysis: Reactions and Experimental Procedures - Dalko, P. I. (Wiley-VCH, 2007)

Comprehensive Enantioselective Organocatalysis: Catalysts, Reactions and Applications - Dalko, P. I. (Wiley-VCH, 2013)

(untitled) - Sibi, M. P.; Cook, G. R.; Liu, P. (Tetrahedron Lett., 1999)

(untitled) - Turgut, Y.; Azizoglu, M.; Erdogan, A.; Arslan, N.; Hosgoren, H. (Tetrahedron: Asymmetry, 2013)

(untitled) - Probst, N.; Madarász, Á.; Valkonen, A.; Pápai, I.; Rissanen, K.; Neuvonen, A.; Pihko, P. M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Kohno, J.; Koguchi, Y.; Nishio, M.; Nakao, K.; Kuroda, M.; Shimizu, R.; Ohnuki, T.; Komatsubara, S. (J. Org. Chem., 2000)

(untitled) - Coste, A.; Couty, F.; Evano, G. (C. R. Chim., 2008)
See for a review.

(untitled) - Coste, A.; Bayle, A.; Marrot, J.; Evano, G. (Org. Lett., 2014)

(untitled) - Miyabe, H.; Takemoto, Y. (Bull. Chem. Soc. Jpn., 2008)

(untitled) - Connon, S. J. (Chem. Commun., 2008)

(untitled) - Liu, X.; Lu, Y. (Org. Biomol. Chem., 2010)

(untitled) - Herrera, R. P.; Sgarzani, V.; Bernardi, L.; Ricci, A. (Angew. Chem., Int. Ed., 2005)

(untitled) - Yevich, J. P.; Yocca, F. D. (Curr. Med. Chem., 1997)

(untitled) - Arendt, J.; Deacon, S. (Chronobiol. Int., 1997)

(untitled) - Laine, A. E.; Lood, C.; Koskinen, A. M. P. (Molecules, 2014)

(untitled) - Roca-López, D.; Marqués-López, E.; Alcaine, A.; Merino, P.; Herrera, R. P. (Org. Biomol. Chem., 2014)

(untitled) - Marqués-López, E.; Alcaine, A.; Tejero, T.; Herrera, R. P. (Eur. J. Org. Chem., 2011)

(untitled) - Ganesh, M.; Seidel, D. (J. Am. Chem. Soc., 2008)

(untitled) - Wittkopp, A.; Schreiner, P. R. (Chem. – Eur. J., 2003)

(untitled) - Loh, C. C. J.; Badorrek, J.; Raabe, G.; Enders, D. (Chem. – Eur. J., 2011)

(untitled) - Joseph, B.; Chapellier, V.; Mérour, J.-Y.; Léonce, S. (Heterocycles, 1998)

(untitled) - Joseph, B.; Alagille, D.; Mérour, J.-Y.; Léonce, S. (Chem. Pharm. Bull., 2000)

(untitled) - Loh, C. C. J.; Raabe, G.; Enders, D. (Chem. – Eur. J., 2012)

(untitled) - Glennon, R. A.; Lee, M.; Rangisetty, J. B.; Dukat, M.; Roth, B. L.; Savage, J. E.; MacBride, A.; Rauser, L.; Hufeisen, S.; Lee, D. K. H. (J. Med. Chem., 2000)

WO Patent - Glennon, R. A.; Roth, B. L. (Selective 5-HT6 Receptor Ligands, 2000)

(untitled) - Chang-Fong, J.; Rangisetty, J. B.; Dukat, M.; Setola, V.; Raffay, T.; Roth, B.; Glennon, R. A. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Cole, D. C.; Lennox, W. J.; Stock, J. R.; Ellingboe, J. W.; Mazandarani, H.; Smith, D. L.; Zhang, G.; Tawa, G. J.; Schechter, L. E. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Dukat, M.; Mosier, P. D.; Kolanos, R.; Roth, B. L.; Glennon, R. A. (J. Med. Chem., 2008)

(untitled) - Ciamician, G.; Plancher, G. (Ber. Dtsch. Chem. Ges., 1896)

(untitled) - Loh, C. C. J.; Atodiresei, I.; Enders, D. (Chem. – Eur. J., 2013)

(untitled) - Vacca, J. P.; Dorsey, B. D.; Schleif, W. A.; Levin, R. B.; McDaniel, S. L.; Darke, P. L.; Zugay, J.; Quintero, J. C.; Blahy, O. M.; Roth, E.; Sardana, V. V.; Schlabach, A. J.; et al. (Proc. Natl. Acad. Sci. U. S. A., 1994)

(untitled) - Dorsey, B. D.; Levin, R. B.; McDaniel, S. L.; Vacca, J. P.; Guare, J. P.; Darke, P. L.; Zugay, J. A.; Emini, E. A.; Schleif, W. A.; Quintero, J. C.; Lin, J. H.; Chen, I.-W.; et al. (J. Med. Chem., 1994)

(untitled) - Jiang, H.; Paixão, M. W.; Monge, D.; Jørgensen, K. A. (J. Am. Chem. Soc., 2010)

(untitled) - Juste-Navarro, V.; Marqués-López, E.; Herrera, R. P. (Asian J. Org. Chem., 2015)

(untitled) - Herrera, R. P.; Monge, D.; Martín-Zamora, E.; Fernández, R.; Lassaletta, J. M. (Org. Lett., 2007)

(untitled) - Sibi, M. P.; Itoh, K. (J. Am. Chem. Soc., 2007)

(untitled) - Shi, X.; He, W.; Li, H.; Zhang, X.; Zhang, S. (Tetrahedron Lett., 2011)

(untitled) - Liu, X.-L.; Wu, Z.-J.; Du, X.-L.; Zhang, X.-M.; Yuan, W.-C. (J. Org. Chem., 2011)

(untitled) - Larsen, T. O.; Frydenvang, K.; Frisvad, J. C.; Christophersen, C. (J. Nat. Prod., 1998)

(untitled) - Ariza, M. R.; Larsen, T. O.; Petersen, B. O.; Duus, J. Ø.; Christophersen, C.; Barrero, A. F. (J. Nat. Prod., 2001)

(untitled) - Larsen, T. O.; Petersen, B. O.; Duus, J. Ø.; Sørensen, D.; Frisvad, J. C.; Hansen, M. E. (J. Nat. Prod., 2005)

(untitled) - Dong, Z.; Qiu, G.; Zhou, H.-B.; Dong, C. (Tetrahedron: Asymmetry, 2012)

(untitled) - Owens, T. D.; Hollander, F. J.; Oliver, A. G.; Ellman, J. A. (J. Am. Chem. Soc., 2001)

(untitled) - Owens, T. D.; Souers, A. J.; Ellman, J. A. (J. Org. Chem., 2003)

(untitled) - Schenkel, L. B.; Ellman, J. A. (Org. Lett., 2003)

(untitled) - Pei, D.; Wang, Z.; Wei, S.; Zhang, Y.; Sun, J. (Org. Lett., 2006)

(untitled) - Solà, J.; Revés, M.; Riera, A.; Verdaguer, X. (Angew. Chem., Int. Ed., 2007)

(untitled) - Tan, K. L.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2007)

(untitled) - Robak, M. T.; Trincado, M.; Ellman, J. A. (J. Am. Chem. Soc., 2007)

(untitled) - Soh, J. Y.-T.; Tan, C.-H. (J. Am. Chem. Soc., 2009)

(untitled) - Almaşi, D.; Alonso, D. A.; Nájera, C. (Tetrahedron: Asymmetry, 2006)

(untitled) - Almaşi, D.; Alonso, D. A.; Gómez-Bengoa, E.; Nagel, Y.; Nájera, C. (Eur. J. Org. Chem., 2007)

(untitled) - Blarer, S. J.; Seebach, D. (Chem. Ber., 1983)